The performance of the copulas in estimating the joint probability of extreme waves and surges along east coasts of the mainland China. (1st October 2021) - Li, Jiangxia; Pan, Shunqi; Chen, Yongping; Gan, Min
Abstract: In designing coastal and nearshore structures, the joint probability of the wave heights and storm surges is essential in determining the possible highest total water level. The key elements to accurately estimate the joint probability are the appropriate sampling of the extreme values and selection of probability functions for the analysis. This study is to provide a full assessment of the performance of the different methods employed in the joint probability analysis. The bivariate extreme wave height and surge samples are analysed using 2 different probability distributions and the performance of 4 copulas, namely: Gumbel–Hougaard copula, Clayton copula, Frank copula and Galambos copula, is assessed. The possible highest total water levels for 100-year return period along the coastline of the mainland China are estimated by the joint probability method with the Gumbel–Hougaard copula. The results show that the wave heights and surges are highly correlated in the areas of dense typhoon paths. The distributions of the possible highest total water levels show a higher value in the southeast coast and lower value in the north. The results also indicate that at the locations where the sea states are energetic, the joint probability approach can improve the accuracy of design. Highlights: The dependencies between the extreme wave heights and surges along east coasts of the mainland China are analysed. The performances of 4 copulas in the joint probability analysis of extreme values are assessed. The distribution of extreme water level along the mainland China coast are calculated by joint probability approach. Applying the joint probability approaches to the mid-east and southeast coast can improve the accuracy of estimation.